2020
DOI: 10.1073/pnas.1913716117
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear hydrodynamic instability and turbulence in pulsatile flow

Abstract: Pulsating flows through tubular geometries are laminar provided that velocities are moderate. This in particular is also believed to apply to cardiovascular flows where inertial forces are typically too low to sustain turbulence. On the other hand, flow instabilities and fluctuating shear stresses are held responsible for a variety of cardiovascular diseases. Here we report a nonlinear instability mechanism for pulsating pipe flow that gives rise to bursts of turbulence at low flow rates. Geometrical d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 37 publications
7
47
0
Order By: Relevance
“…Xu et al. (2020) showed that initializing direct numerical simulations with the linear optimal helical disturbance can trigger turbulent flow patterns as those observed in their experiments. In experiments of oscillatory pipe flow, the transition threshold is independent of (with different critical numbers depending on the set-up, see Sergeev 1966; Merkli & Thomann 1975; Hino et al.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Xu et al. (2020) showed that initializing direct numerical simulations with the linear optimal helical disturbance can trigger turbulent flow patterns as those observed in their experiments. In experiments of oscillatory pipe flow, the transition threshold is independent of (with different critical numbers depending on the set-up, see Sergeev 1966; Merkli & Thomann 1975; Hino et al.…”
Section: Resultsmentioning
confidence: 86%
“…Thomas et al (2011) showed that the linear instability of oscillatory pipe flow persists also for pulsatile flow; however, in experiments, transition occurs much earlier (see e.g. Sarpkaya 1966;Stettler & Hussain 1986;Xu et al 2017Xu et al , 2020. Taken together, these results suggest that pulsatile pipe flow undergoes a subcritical transition to turbulence in all regimes.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Active or dynamic control requires auxiliary energy, while passive or static control requires none 17 . Both control schemes applied to flow patterns and fluid instabilities in Newtonian fluids have extensively been studied [18][19][20][21][22][23][24][25] . Also, passive control of viscoelastic fluid flow has been examined [26][27][28][29][30][31] using either geometric modifications 28,29 including spatially modulated cylinders in a Taylor-Couette geometry 30 and disorder in microfluidic flows to inhibit elastic turbulence 31 , or soft boundaries 27 , as well as thermal control 26 .…”
mentioning
confidence: 99%